Carbapenem Resistant Enterobacteriaceae Detection Methods - Kastawa, Ni Wayan Eka Putri Gayatri; Ramona, Yan; Fatmawati., N.N. Dwi (Metamorfosa: Journal of Biological Sciences, 2020)
Carbapenem Resistant Enterobacteriaceae (CRE) is a group of Enterobacteriaceae resistant to Carbapenem antibiotics (Imipenem, Ertapenem, Meropenem, Doripenem). One species of Enterobacteriaceae frequently showing   resistant characteristic to Carbapenem is Klebsiella pneumoniae . Early detection methods on the CRE existence (phenotypically or genetically) are urgently needed. The methods should be able to detect carbapenemases or genes encoding these types of enzymes.  In the recent years, phenotypic characteristics can be done by applying methods, such as Modified Hodge Test (MHT), Carba Nordmann-Poirel (Carba NP), or Modified Carbapenem Inactivation Method (MCIM). To detect the presence of genes encoding production of carbapenemases, Polymerase Chain Reaction (PCR) is the most reliable method available in the recent years. Keywords : Carbapenem Resistant Enterobacteriaceae (CRE), Phenotype, Genothype, Modified Carbapenem Inactivation Method (MCIM), Modified Hodge Test (MHT), Carba Nordmann-Poirel, Polymerase Chain Reaction (PCR).